2012
DOI: 10.17221/13/2011-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Determinant factors of vertical intra industry trade in agricultural sector: A study of Iran and her main trading partners

Abstract: Abstract:The present study has investigated the country specific determinants of the vertical and total intra-industry trade between iran and its main trading partners (including 24 countries) in the agricultural products group during the time period [2001][2002][2003][2004][2005][2006][2007]. For this purpose, first we have measured the types of the intra-industry trade. Then we have examined the determinants of the vertical and total intra-industry trade in the agricultural sector by using the panel techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 32 publications
2
23
2
1
Order By: Relevance
“…Similarly to studies on manufacturing sectors, the results do not support comparative advantage explanation of vertical IIT (Milgram-Baleix and MoroEgido, 2010). Contrary to Fertő (2005) and Rasekhi and Shojaee (2012), agriculture-related variables are negative for most specifi cations. However, the results are similar to previous studies (e.g.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…Similarly to studies on manufacturing sectors, the results do not support comparative advantage explanation of vertical IIT (Milgram-Baleix and MoroEgido, 2010). Contrary to Fertő (2005) and Rasekhi and Shojaee (2012), agriculture-related variables are negative for most specifi cations. However, the results are similar to previous studies (e.g.…”
Section: Resultsmentioning
confidence: 67%
“…Leitão (2011) found that the agricultural IIT of the United States was positively infl uenced by average GDP, foreign domestic investment (FDI) and trade imbalance, while it had a negative relationship with differences in per capita GDP. Rasekhi and Shojaee (2012) showed that VIIT between Iran and its main trading partners and was positively infl uenced by land endowments, but negatively affected by the economic size of trading partners. Caetano and Galego (2007) found that determinants of HIIT and VIIT also differed within an enlarged Europe, although both had a statistically signifi cant relationship with a country's size and FDI.…”
Section: Country-and Industry-specifi C Determinants Of Intra-industrmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies support the view that agricultural markets can be characterized by imperfect competition (Sexton, 2013) and IIT has an increasing role in agricultural trade for both developed and developing countries (e.g. Leitão 2011;Rasekhi and Shojaee 2012;Wang 2009;Varma 2012). Moreover, the majority of literature is focused on a single country and many simply neglect the importance of the horizontal/vertical distinction of IIT.…”
mentioning
confidence: 99%
“…In fact, IIT happens when a country simultaneously imports and exports identical goods. In this kind of trade, a country can be the importer of the same good which exports it [4].…”
Section: Introductionmentioning
confidence: 99%